2018
DOI: 10.1038/s41467-018-05458-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive Dengue virus-specific CD8+ T cells protect against Zika virus during pregnancy

Abstract: As Zika virus (ZIKV) emerges into Dengue virus (DENV)-endemic areas, cases of ZIKV infection in DENV-immune pregnant women may rise. Here we show that prior DENV immunity affects maternal and fetal ZIKV infection in pregnancy using sequential DENV and ZIKV infection models. Fetuses in ZIKV-infected DENV-immune dams were normal sized, whereas fetal demise occurred in non-immune dams. Moreover, reduced ZIKV RNA is present in the placenta and fetuses of ZIKV-infected DENV-immune dams. DENV cross-reactive CD8+ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 74 publications
8
109
1
Order By: Relevance
“…DENV-immune CD8 + T cells were required for this cross-protection. However, mice challenged 80 days after DENV priming were not protected, indicating the transient nature of cross-protection again 40 .…”
Section: Discussionmentioning
confidence: 99%
“…DENV-immune CD8 + T cells were required for this cross-protection. However, mice challenged 80 days after DENV priming were not protected, indicating the transient nature of cross-protection again 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, mice deficient in these molecules had increased viral burden 124,125 . Heterologous, memory T-cell responses also can have protective functions, as cross-reactive DENV-immune CD8 + T cells restrict ZIKV infection and disease, including in pregnancy 126,127 . Reciprocally, ZIKV-immune CD8 + T cells can protect against DENV infection in mice 128 .…”
Section: Immune Response To Flavivirus Infectionmentioning
confidence: 99%
“…Yet in another study in Ifnar1 -/-(A129) or Ifnar1 -/-Ifngr -/-(AG129) mice, whilst inactivated ZIKV vaccination enhanced dengue disease severity, ADE was not observed after ZIKV infection in animals that were passively immunized or pre-infected with DENV 181 . Apart from the contrasting results, a major caveat to the passive transfer of antibody model is that these mice lack immune, cross-reactive CD8 + T cells, which can limit the pathological effects of ADE in the context of DENV immunity and subsequent ZIKV infection, including during pregnancy 127,192 .…”
Section: Emerging and Re-emerging Threatsmentioning
confidence: 99%
“…The protective role of the cellular immune response controlling the viral burden of ZIKV in mice has been reported (76, 77). More recently mouse models have shown that prior DENV immunity can protect against ZIKV infection during pregnancy, and CD8+ T cells are sufficient for this cross-protection (78). Currently, it is well documented that pre-exposure to DENV both in macaques and humans results in a qualitative modification of the humoral and cellular immune response to ZIKV (24, 27-29) .…”
Section: Discussionmentioning
confidence: 99%